Cherry Blossom Creation Boutique / Anis Nurkhalidah Ahmad Fazil ... [et al.] - Ahmad Fazil, Anis Nurkhalidah; Nor Azman, Hanis Hasanah; Saipudin, Nurul Farisha; Azmin Sani, Siti Zulaiha; Hud, Syazarisya (2021)
Cherry Blossom Creation Boutique is a Damansara Utama-based bridal gown boutique. The boutique is managed by five friends. In terms of services, Cherry Blossom Creation Boutique focuses on designing and producing wedding dresses and supplying the highest quality gowns to bridal galleries throughout the nation. Additionally, the shop offers other wedding clothing, including an array of accessories, bridesmaids' attire, bridal footwear, and bridal accessories. Cherry Blossom Creation Boutique began operations in 2016 and has been operating for five years. They established this company with the goal of making customers happy while wearing a stunning wedding gown on their wedding day. This boutique's main objectives are to serve as a one-stop shop for the bride and other female members of the wedding party once the bride has bought her gown. This is because they understand that every woman has a dream of having a luxurious and elegant wedding, which motivates them to do all possible to offer first-class goods and services to their customers. Other than that, they recognize that delivering glamorous, high-quality dresses and other services is a very important occasion. As a result, the boutique will guarantee that the high-quality customized wedding dresses will fit the customers perfectly. Next, as we all know, a business strategy is required for all entrepreneurs. It is created for a group of individuals, including the business owners, bankers, creditors, suppliers, customers, and workers. Moreover, a marketing strategy, an operational plan, an organizational plan, and a financial plan are all included in this business plan. Like other businesses, Cherry Blossom Creation Boutique also cannot avoid difficulties in their everyday operations. As a result, the boutique has chosen to utilize SWOT analysis as a business guideline to get a better understanding of the opportunities and threats that the company faces on an external level. These five friends also make use of the Business Model Canvas to discuss and create more ideas to enhance their company while also increasing their operational profit. This is because the financial plan is also critical for them to understand the business's net profit in order to understand their money's cash flow. In a nutshell, the company hopes that their products and services will enhance business in the future and that they will seize the chance to open many branches around the world.